AN ANALYSIS ON THE USE OF CODE SWITCHING IN TEACHING ENGLISH TO YOUNG LEARNERS: A CASE STUDY AT SD IT AULADI - Prabowo Lukito; Annisa Astrid; Rizqy Dwi Amrina (Wiralodra English Journal, 2022)
Teachers have tended to use code switching in teaching and learning English because it is an essential and inseparable part of language teaching. The purpose of this study was to determine the factors that influence English teacher switched the language when teaching English to young learners. The study was structured as a qualitative case study. The participants of the study were the English teacher and the students of the class taught by the teacher. Thematic analysis was used to analyse the data gathered through observations and interviews. The study's findings indicated that code switching practices were influenced by students' lack of English competency, teacher's lack of English competency, ease of instruction and communication, ease of maintaining students' discipline in the classroom, and ease of expressing teacher's feelings. Keywords: Code Switching, English Language Teaching, Young Learners.